Old Uigur Administrative Orders from Turfan - Berker Keskin (İstanbul Üniversitesi Edebiyat Fakültesi Türk Dili ve Edebiyatı Dergisi)
Matsui, Dai (2023). Old Uigur Administrative Orders from Turfan. Berliner Turfantexte XLVIII. Turnhout: Brepols. 294 s. ISBN: 978-2-503-60489-3.